RufGen: A plug-in for rough surface generation in Abaqus/CAE - Youngbin Lim; Sangyul Ha (SoftwareX, 2023)
Surface interaction is an important topic in engineering, and it is generally recognized that the roughness of a surface has a significant impact on numerous physical phenomena, including contact, wear, friction, and heat transmission. AbaqusTMis a robust finite element program commonly used in industry and academics to simulate these phenomena. Nonetheless, generating rough surface models with Abaqus/CAE is quite challenging and may necessitate the usage of auxiliary tools. We present a plug-in called RufGen for automatic finite element model generation of rough surfaces in an Abaqus/CAE environment. RufGen supports all accessible Abaqus elements, from 2D-wire to 3D-solid. The rough surface can be constructed by importing the measured surface profile data as a text file or by entering geometrical parameters through a graphical user interface. An illustrative example is provided for describing the use of RufGen, an open source project available on GitHub.